A intersetorialidade das políticas sociais na urbanização de favelas: uma possibilidade para a concretização do direito à cidade? - Oliveira, Priscila Beralda Moreira de (2011)
The present dissertation had as study object the intersect lines of the social politics in the urbanization of slum as full potential element of the right to the city. The inquiry centered in the existing limits for a articulated performance of the social politics in the urbanization of the Slum Shot to the Pigeon with focus in the Plan of the Social Work, having as central idea to analyze if the social politics of urbanization of slums, together with excessively social politics presents in the territory face the socio-territorial inequalities and materialize the right to the city, being this one of the objectives of the Habitation Politics.The methodology enclosed bibliographical research, documentary research, field research by means of interviews with coordinator of the urbanization project, social technical team and resident of the area. For understanding of our object of study, we work, with a conceptual referential that it enclosed, beyond the concept intersect lines, the concepts of territory and right to the city. The research evidenced that the intersect lines management is not a reality in the urbanization project, does not exist actions articulated with excessively the social politics, keeping the fragmented and focused performance. For the citizens of the research, actions articulated between the different social politics would become the attendance the families most effective, however, to become a reality, it needs to be a line of direction for the work, becoming the urbanization of determined area responsibility of all the politics, what it would provide a full potential to the intervention and the possibilities, so that the right to the city would be accomplished. To think intersect line still is a great challenge, is a process that demands learning mainly and good will politic from de governments and publics managers. The management of intersect line needs to be considered as presupposes for the urbanization of slums, being basic to face the poverty situations, making possible that segregated areas pass to integrate to the totality of the city